Peirce's Semiotic Analysis Of The New Halal Indonesia Logo - Patriansah, Mukhsin; Nurhawa, Adevia; Kuncoro, M.Septian Adi (LPPM Institut Seni Indonesia Padangpanjang, 2024)
Since it was inaugurated on March 1 2022, Indonesia's new halal logo has attracted a lot of controversy. This is inseparable from the visual appearance of the logo which is very strong in Javanese culture by taking the shape of a mountain and a lurik surjan motif as the big idea. However, the signs and meanings in them are still conventional in accordance with Islamic values such as the value of divinity, faith and devotion, as well as the value of tolerance. On the other hand, the new Indonesian halal logo design is able to represent the halal and haram rules and laws themselves based on Islamic law. This research uses Peirce's semiotic approach with the boundaries of signs as objects, namely icons, indices and symbols. The method used is a qualitative research method with an interpretive analysis approach. From the results of the research carried out, there is a new marking system through observation and analysis carried out in the form of signs of Allah's pronunciation and the shape of the mosque dome. Overall, the visual appearance of the new Indonesian halal logo meets the design principles of being simpler, timeless, elegant, unique and attractive, proportional and relevant. In this way, the visual identity of the halal logo can make it easier for Muslims to recognize and identify halal products that are suitable for consumption.